Comparative Analysis of the Development Areas of Environmental Audit in International Practice and in the Republic of Kazakhstan - Zhumabekova, Gaukhar Zh.; Barysheva, Salima K.; Yesturliyeva, Aigul I.; Akimova, Bibigul Zh.; Korabayev, Beibit S. (Journal of Environmental Accounting and Management, 2026)
The development and expansion of the environmental audit abroad are mainly explained by the tightening of environmental legislation, the unification of requirements and standards in the trade area, credit, and financial policy in connection with the creation of a unified environmental space. If the environmental audit has become a real management tool abroad, in Kazakhstan, the development of a regulatory framework, the establishment of appropriate standards, and documents in this area are at an early stage, although there is some practical experience. The relevance of environmental audits at Kazakh enterprises has economic, environmental, and social aspects. The state is interested in the development of environmental audit and the creation of an appropriate regulatory framework for its functioning. Environmental accounting has not yet acquired a final understanding and logical completeness in the form of a complex knowledge system. The main tasks of the environmental audit are similar to the tasks of the audit in general, but they have their specific features, namely collecting reliable information about the company’s production and developing conclusions and prerequisites for making management decisions about the actual environmental state of the enterprise. For Kazakh institutions of external financial control, environmental audit is a new area. The active development of environmental audit methodology at the national level is based on the achievements of International Organisation of Supreme Audit Institutions (INTOSAI).